ZZFS: A Hybrid Device and Cloud File System For Spontaneous Users - Mazurek, Michelle L.; Thereska, Eno; Gunawardena, Dinan; Harper, Richard; Scott, James (Proceedings of the 10th Usenix Conference on File and Storage Technologies (FAST'12), 2012)
Good execution of data placement, caching and consistency policies across a user’s personal devices has always been hard. Unpredictable networks, capricious user behavior with leaving devices on or off and non-uniform energy-saving policies constantly interfere with the good intentions of a storage system’s policies. This paper’s contribution is to better manage these inherent uncertainties. We do so primarily by building a low-power communication channel that is available even when a device is off. This channel is mainly made possible by a novel network interface card that is carefully placed under the control of storage system protocols. The design space can benefit existing placement policies (e.g., Cimbiosys [21], Perspective [23], Anzere [22]). It also allows for interesting new ones. We build a file system called ZZFS around a particular set of policies motivated by user studies. Its policies cater to users who interact with the file system in an ad hoc way — spontaneously and without pre-planning.